Dichotomous cis-regulatory motifs mediate the maturation of the neuromuscular junction by retrograde BMP signaling. Issue 17 (27th August 2022) - Vuilleumier, Robin; Miao, Mo; Medina-Giro, Sonia; Ell, Clara-Maria; Flibotte, Stephane; Lian, Tianshun; Kauwe, Grant; Collins, Annie; Ly, Sophia; Pyrowolakis, George; Haghighi, A Pejmun; Allan, Douglas W
Abstract: Retrograde bone morphogenetic protein (BMP) signaling at the Drosophila neuromuscular junction (NMJ) has served as a paradigm to study TGF-β-dependent synaptic function and maturation. Yet, how retrograde BMP signaling transcriptionally regulates these functions remains unresolved. Here, we uncover a gene network, enriched for neurotransmission-related genes, that is controlled by retrograde BMP signaling in motor neurons through two Smad-binding cis -regulatory motifs, the BMP-activating ( BMP-AE ) and silencer ( BMP-SE ) elements. Unpredictably, both motifs mediate direct gene activation, with no involvement of the BMP derepression pathway regulators Schnurri and Brinker. Genome editing of candidate BMP-SE and BMP-AE within the locus of the active zone gene bruchpilot, and a novel Ly6 gene witty, demonstrated the role of these motifs in upregulating genes required for the maturation of pre- and post-synaptic NMJ compartments. Our findings uncover how Smad-dependent transcriptional mechanisms specific to motor neurons directly orchestrate a gene network required for synaptic maturation by retrograde BMP signaling.